Application of Mosaic Technique to Develop Children's Fine Motor Skills in PAUD Nurul Iman (Jurnal Sustainable, 2023)
From birth to six years of age, children participate in Early Childhood Education (ECE), a pre-basic education program that aims to prepare them for future learning through formal, non-formal, and informal means by providing them with educational stimuli that support their physical and spiritual development. Along with physical growth, children undergo a period of increased self-awareness, social competence, and environmental understanding throughout the early years of life. Researchers at PAUD Nurul Iman Desa Talang Baru want to learn more about the effects of mosaic techniques on the development of fine motor skills in young children so they can plan an appropriate study. The term "Classroom Action Research" comes from the English word "classroom research," meaning "research done in a class to find out the consequences of actions applied to a research subject in the class." This study draws on classroom actions to answer the research question. The study and conversations done led to the conclusion that the mosaic approach may help the group A children of TK ABA Khadijah Bangunjiwo Timur Kasihan Bantul strengthen their fine motor abilities.